PTH-314 Curative management for stage IV rectal cancer – has the potential improved?. (22nd June 2015) - Rajendran, N; Yap, K; Kaneko, Y; Thomson, B; Ngan, S; Michael, M; Lynch, C; Warrier, SK; Heriot, AG
Abstract : Introduction: The aim of the study was to assess the change in survival outcomes of patients with stage IV rectal cancer treated with curative intent over a 25 year period. Method: A retrospective review was undertaken on all patients referred to an oncology centre between 1987 and 2013 with Stage IV rectal cancer at their initial presentation that were treated for cure. Data was collected on demographics, therapeutic interventions, and survival. Information included initial treatment if undertaken at the referring hospital. Data was divided across time points (1987–2000, 2001–2013) and Kaplan-Meier analysis was undertaken for survival across the period of review. Results: A total of 108 patients were identified with stage IV rectal cancer at the time of referral [mean age 59.7 (range 30–87)], 70 male:38 female. At referral 83 patients had liver metastases, 44 had lung metastases and 19 had other metastases. Follow-up was available in 96 patients. Neoadjuvant chemoradiotherapy was given to 66% of patients. Of the 97 patients for whom data were available, 89 patients had resection of the rectal primary (92.7%). 56% had adjuvant chemotherapy, 10% had adjuvant chemoradiotherapy. Metastasectomy was undertaken in 40.9% patients (34/83 patients) with liver mestastases and 36.4% (16 /44 patients) with lung metastases. Overall 1 year, 3 year and 5 year survival improved significantly over time (1987–2000 vs. 2001–2013 cohorts; 1 year 80% vs. 96%; 3 year 25% vs. 57%, 5 year 17% vs. 46% respectively [p < 0.01]). Conclusion: The survival outcomes for patients treated for stage IV rectal cancer demonstrate more patients have been treated with curative intent and 5-year survival has improved significantly. Disclosure of interest: None Declared.